2018
DOI: 10.15171/apb.2018.035
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Regenerative Effects of Intra Articular Injection of Co-Cultured Adipose Derived Stem Cells with Chondron for Treatment of Induced Osteoarthritis

Abstract: Purpose: Adipose tissue derived stem cells (ASCs) and chondrocytes are best cells for articular cartilage regeneration. Chondrocyte with peri-cellular matrix (PCM) is called chondron provides ideal microenviroment than chondrocytes. We aimed to evaluate the regenerative effects of intra-articular injection of ASCs co-cultures with chondron in induced osteoarthritis (OA).Methods: ASC, from the peri-renal fat of male rat and chondron from primary newborn rat hyaline cartilage were isolated. ASCs were cultured fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…So, the changes of GAG levels in synovial fluids reflect catabolic activity in cartilage ECM [42]. In this study, overexpression of IGF-1 and miR-140 each individually reduces the content of GAG in synovial fluid, decreases COL1A2 (fibrocartilaginous markers) and COL10A1 (cartilage hypertrophy markers) synthesis [43, 44], and increases ACAN and COL2A1 synthesis compared with the negative control group (pBudCE4.1 transfection group) which were beneficial for cartilage repair, and fewer GAG in the synovial fluid, less COL1A2 and COL10A1, and more ACAN and COL2A1 synthesis were detected in IGF-1 combined with miR-140 group. These results imply that the repair tissue filling in the cartilage defects possesses characteristics of hyaline cartilage, and IGF-1 and miR-140 have synergistic effects for better therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…So, the changes of GAG levels in synovial fluids reflect catabolic activity in cartilage ECM [42]. In this study, overexpression of IGF-1 and miR-140 each individually reduces the content of GAG in synovial fluid, decreases COL1A2 (fibrocartilaginous markers) and COL10A1 (cartilage hypertrophy markers) synthesis [43, 44], and increases ACAN and COL2A1 synthesis compared with the negative control group (pBudCE4.1 transfection group) which were beneficial for cartilage repair, and fewer GAG in the synovial fluid, less COL1A2 and COL10A1, and more ACAN and COL2A1 synthesis were detected in IGF-1 combined with miR-140 group. These results imply that the repair tissue filling in the cartilage defects possesses characteristics of hyaline cartilage, and IGF-1 and miR-140 have synergistic effects for better therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore Jacer et al . [ 26 ] reported articular surfaces fibrillations, decreased cartilage thickness and loss of tidemarks integrity in the knee joints of osteoarthritic rats, 6 weeks after OA induction by intra-articular injection of collagenase II.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that chondrocyte/alginate spheres even with genetically modified chondrocytes can be implanted into the defective regions of osteochondral articular cartilage to promote the repair of defective cartilage in vivo [30]. Recent studies have shown that co-administration of chondrons and adipose-derived stem cells or MSCs [52,53] increases articular hyaline cartilage formation. In this study, we found that implantation with chondrons/chondrocytes alginate spheres significantly accelerated the repairs of defective knee cartilage in rabbits by increasing the cartilage matrix and thicknesses and reducing the Wakitani scores in a trend of time dependence.…”
Section: Discussionmentioning
confidence: 99%